2022
DOI: 10.3855/jidc.15411
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and risk factors associated with severe disease and outcome of patients with COVID-19

Abstract: Introduction: Since the beginning of the pandemic, factors associated with mortality in patients with corona virus infection disease 2019 (COVID-19) have been investigated. Comorbidities and increased age have been frequently reported to be associated with mortality. We aimed to evaluate the factors associated with unfavorable outcome of patients with COVID-19 at an early period of the pandemic. Methodology: This single center, retrospective, observational study was conducted among laboratory confirmed C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Although several scientific studies have reported an association between certain comorbidities and the development of severe forms of SARS-CoV-2 infection [44][45][46][47][48][49][50], literature studies on the association between comorbidities and the risk of reinfection are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Although several scientific studies have reported an association between certain comorbidities and the development of severe forms of SARS-CoV-2 infection [44][45][46][47][48][49][50], literature studies on the association between comorbidities and the risk of reinfection are limited.…”
Section: Discussionmentioning
confidence: 99%
“…All thirty-three studies reported gender differences (men were taken as reference group in this study), and the result of our analysis showed that men were more likely to have severe disease than women (OR = 1.52, 95 % CI:1.34–1.73; I 2 = 85 %, p < 0.001) [ 14 46 ]. In this study, age was statistically significant (SMD = 0.62, 95 % CI: 0.43–0.82 of which OR = 3.06, 95 % CI: 2.18–4.40; I 2 = 97 %; p < 0.001) [ 14 25 , 27 46 ]. Of all articles included in this study, the mean age of patients with severe affection was higher than that of patients with non-severe affection, except for the studies of Takacs et al, 2023 and Xu et al, 2023 [ 36 , 41 ].…”
Section: Resultsmentioning
confidence: 58%
“…In Fig. 5 , our results indicate that shock with an OR of 28.08 (95 % CI: 19,99–78,41; I 2 = 86 %, p < 0.001) [ 18 , 21 , 24 , 35 , 38 , 40 , 41 ], acute kidney injury (AKI) with OR = 16.91 (95 % CI: 1.87–152.45; I 2 = 63 %; p = 0.07) [ 18 , 21 , 38 , 40 ] and acute respiratory distress syndrome (ARDS) with OR = 13.09 (95 % IC: 5.87–29.18; I 2 = 94 %, P < 0.001) [ 14 , 18 , 21 , 23 25 , 27 , 30 , 31 , 38 , 40 , 43 ] were the principal complications associated with severe and life threatening disease in COVID-19 patients. In addition to the aforementioned complications, cardiac rhythm disturbance (arrhythmia) (OR = 7.47; 95 % CI: 2.96–18.83; I 2 = 34 %, p = 0.20) [ 14 , 18 , 24 , 30 , 38 ] was one of the complications associated with the severity of COVID-19 disease in some patients, although the result was not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that several laboratory tests, such as WBC count, platelet count, and C-reactive protein (CRP), are helpful to predict whether COVID-19 patients are likely to be admitted to the ICU [ 35 , 37 ]. Patients with a high WBC count and CRP are at a higher risk of severe disease and being admitted to the ICU [ 37 , 38 ]. Our results indicate an association between elevated white blood cell and neutrophil counts with the severity of the disease and admission to the ICU.…”
Section: Discussionmentioning
confidence: 99%